Invited review: MnmE, a GTPase that drives a complex tRNA modification reaction. Issue 8 (20th May 2016) - Fislage, Marcus; Wauters, Lina; Versées, Wim
ABSTRACT: MnmE is a multi‐domain GTPase that is conserved from bacteria to man. Together with its partner protein MnmG it is involved in the synthesis of a tRNA wobble uridine modification. The orthologues of these proteins in eukaryotes are targeted to mitochondria and mutations in the encoding genes are associated with severe mitochondrial diseases. While classical small GTP‐binding proteins are regulated via auxiliary GEFs and GAPs, the GTPase activity of MnmE is activated via potassium‐dependent homodimerization of its G domains. In this review we focus on the catalytic mechanism of GTP hydrolysis by MnmE and the large scale conformational changes that are triggered throughout the GTPase cycle. We also discuss how these conformational changes might be used to drive and tune the complex tRNA modification reaction. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 568–579, 2016.